IMPROVING LEARNING OUTCOMES THROUGH PROBLEM BASED LEARNING ON EARTH AND SOLAR SYSTEM MATERIALS - Arianti, Lisa; Theo Jhoni Hartanto; Pri Ariadi Cahya Dinata (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2025)
This research aims to improve the learning outcomes of class VII-1 students at SMP Negeri 5 Palangka Raya on Earth and Solar System material by using the Problem Based Learning (PBL) learning model. The research subjects consisted of 28 students, consisting of 14 male students and 14 female students, who were part of class VII-1 of SMP Negeri 5 Palangka Raya. The type of research used is Classroom Action Research which is carried out in two cycles, where each cycle consists of two meetings. Each cycle includes planning, implementation, observation and reflection stages. The research results showed that the application of the Problem Based Learning (PBL) learning model in cycles I and II succeeded in improving student learning outcomes. The average value of learning outcomes for class VII-1 students increased in each cycle, namely in cycle I (77.30) and cycle II (80.76). Apart from that, the level of learning completion of students also increased, from 88.46% in cycle I to 92.30% in cycle II. Thus, it can be concluded that the application of the Problem Based Learning (PBL) learning model can improve the learning outcomes of class VII-1 students on Earth and Solar System material at SMP Negeri 5 Palangka Raya for the 2023/2024 academic year.